Comunicação, consumo e religião: narrativas de peregrinos sobre o consumo moral da fé no Santuário de Santa Paulina - Santos, Maria Neusa dos (2015)
The increasing advance of religious consumption in Brazil has contributed to the growth in the number of pilgrimages to sanctuaries in search of response to human aspirations. This progress, to a certain extent, contributes to the moral consumption of faith through religious symbols and virtuous acts, which promote the satisfactory meeting in resolution of the personal needs of the pilgrims in their quest for good life . The studies of reception, combined with an interrelation between communication, consumption and religion, were taken as foundations, based on authors such as Baccega, Carranza, Aristotle, Chauí, Slater, Martin-Barbero, Douglas & Isherwood, Martino, Ricoeur and Hook. The research has its corpus composed by the narratives of pilgrims to the Sanctuary of Santa Paulina in Vigolo, Nova Trento (SC), about the practices of moral consumption of faith, using the qualitative research method. The aim was to get closer to the object, to enable the analysis of moral consumption processes of faith through the virtues lived by the saint and persuade by the pilgrims, as well as the socio-cultural context and the non-mediatic communication present in this object. The analysis of theories of narrative was used as methodology applied to the corpus of the research.